2020
DOI: 10.7596/taksad.v9i3.2719
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Communicative Culture of Students by Means of Project Teaching in Higher Educational Establishments

Abstract: The article is devoted to the problem of forming the communicative culture of future teachers in the process of project teaching in higher educational establishments. Methodological approaches to the definition of the concept of "communicative culture" are analyzed, its qualitative characteristics are determined and examples of discussions in the scientific environment on the characteristics of this phenomenon are given. The authors claim that the component of communicative culture is communicative competence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, if students are to interact fully with educational technology content, Buliva (2020) recommended that instructors and content providers be aware of their students' cultural backgrounds. On the other hand, Maksymenko et al (2020) found that project teaching is regarded by instructors and students alike as one of the most successful ways to shape the communicative cultures of prospective graduate students.…”
Section: The Relationship Between Cultural Values (Educational Value)...mentioning
confidence: 99%
“…However, if students are to interact fully with educational technology content, Buliva (2020) recommended that instructors and content providers be aware of their students' cultural backgrounds. On the other hand, Maksymenko et al (2020) found that project teaching is regarded by instructors and students alike as one of the most successful ways to shape the communicative cultures of prospective graduate students.…”
Section: The Relationship Between Cultural Values (Educational Value)...mentioning
confidence: 99%
“…In this respect, the research will focus on the development of scientific creativity based on speech culture and its existence in students, and in this context, students will be approached with the hope of being a light. Maksymenko, Bei, Khimchuk, and Vovchok (2020) devoted their work to the problem of creating a communication culture of future teachers in the project teaching process. They aimed to examine methodological approaches to the definition of the concept of 'communicative culture', and as a result, they came to the conclusion that project teaching is defined by both students and teachers as one of the effective ways to create the communication culture of future graduate students.…”
Section: Introductionmentioning
confidence: 99%
“…Various problems of modern students have been highligh ted in the works of Ukrainian researchers. In particular, features of development of students' autonomy (Івашкевич & Онуфрієва, 2021), psycholinguistic features of students' acquisition of visual-semantic image of a hieroglyph in studying Japanese (Долинська, Наумова & Шевченко, 2020), formation of communicative culture of students by means of project teaching in higher educational establishments (Maksymenko, Bei, Khimchuk & Vovchok, 2020), influence of the professional orientation of students of different gender on their ideas of happiness (Stroianovska, Dolynska, Shevchenko, Andriiashyna, Melnyk & Tsybuliak, 2020), psychological characteristics of using Internet by students (Oнуфрієва, Дідик, & Чеканська, 2019), students' ideas about life success (Stroyanovska, Dolynska, Shev chenko, Yermakova, Matiash-Zaiats & Kriukova, 2021).…”
Section: Introductionmentioning
confidence: 99%